EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN SIKAP KEDISIPLINAN ANAK ASUH PANTI ASUHAN AISYIYAH PUTRA BUKITTINGGI - Febrianti , Yeni; Syawaluddin, Syawaluddin (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine the effectiveness of group guidance services to improve disciplinary attitudes among children at the Aisyiyah Putra Bukittinggi Orphanage. The approach used in this research is a quantitative approach. The quantitative approach is systematic scientific research into parts and phenomena and their relationships. The type of research used in this research is experimentation. The research design used in this research is a pre-experimental design with a one-group pre-test pro-test model. The data collection method uses a questionnaire. The results of the research are, the results of the Wilcoxon test calculation which obtained a significant result of 0.012. Based on applicable regulations, it is known that the Wilcoxon sig test. P-value 0.012 < 0.05 according to these results it can be said that the use of group guidance services to improve children's disciplinary attitudes was successful. It can be concluded that group guidance services can improve children's disciplinary attitudes at the Aisyiyah Putra Bukittinggi Orphanage.